2021
DOI: 10.1093/cid/ciab629
|View full text |Cite
|
Sign up to set email alerts
|

The Adjuvanted Recombinant Zoster Vaccine Confers Long-Term Protection Against Herpes Zoster: Interim Results of an Extension Study of the Pivotal Phase 3 Clinical Trials ZOE-50 and ZOE-70

Abstract: Background This is an ongoing follow-up study (NCT02723773) evaluating persistence of efficacy and immune responses for six additional years in adults vaccinated with the glycoprotein E (gE)-based adjuvanted recombinant zoster vaccine (RZV) at ≥50 years of age in two pivotal efficacy trials (ZOE-50/70). The present interim analysis was performed after ≥2 additional years of follow-up (between 5.1 and 7.1 years [mean] post-vaccination) and includes partial data for year (Y)8 post-vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 14 publications
2
55
0
4
Order By: Relevance
“… 19–21 The primary clinical trial results from the interim analysis of the ZOE-LTFU study suggests that the VE estimates at 8 years post vaccination were 84.3% overall. 10 In this manuscript, we have provided more granular data from that study demonstrating that VE estimates at 8 years post vaccination were 87.5% in individuals aged 50–69 and 78.9% in individuals aged ≥70 YOA (see supplementary Table S1). Szucs et al, in a review of HZ vaccine cost-effectiveness manuscripts noted that a limitation of most modeling studies was that outdated input data were used.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 19–21 The primary clinical trial results from the interim analysis of the ZOE-LTFU study suggests that the VE estimates at 8 years post vaccination were 84.3% overall. 10 In this manuscript, we have provided more granular data from that study demonstrating that VE estimates at 8 years post vaccination were 87.5% in individuals aged 50–69 and 78.9% in individuals aged ≥70 YOA (see supplementary Table S1). Szucs et al, in a review of HZ vaccine cost-effectiveness manuscripts noted that a limitation of most modeling studies was that outdated input data were used.…”
Section: Discussionmentioning
confidence: 96%
“…An interim analysis of ZOE-LTFU, following up the original ZOE study populations, presented the VE estimates out to 8 years following initial vaccination. 10 Details of the study design and methodology are provided in Boutry et al 10 We used the observed ZOE-LTFU clinical trial VE analysis by year separated into the age groups 50–69 and ≥70 YOA (see supplementary Table S1) to estimate the VE at time 0 (i.e. take) and slope (annual waning) of efficacy over time using a linear regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the previous cost-effectiveness analysis of RZV in Japanese adults does not reflect the most up-to-date parameters of RZV efficacy and waning rate. Interim results from the ongoing long-term follow-up (LTFU) of the ZOE-50 and ZOE-70 studies (ZOE-LTFU; NCT02723773) have shown that RZV efficacy remained high for up to 8 years post-vaccination [ 19 ]. When the updated vaccine efficacy results were incorporated into a Markov model, RZV was found to improve public health and cost-effectiveness results compared with previous analyses in the German population aged ≥ 50 years [ 20 ], although the effects in the Japanese population have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether the cause of this difference is due to the booster immunization route of natural varicella infection or subcutaneous injection, or the wild or attenuated vaccine strain of VZV, or immunoreactivity of the target age groups between< 50 and> 50. The HZ-preventive effect of another HZ-preventive vaccine, gE-based Shingrix®, was sustained for at least 7 years [24] . Since the HZ incidence continues to rise, the preventive effect of varicella contact on HZ seems to be as persistent as Shingrix®.…”
Section: Discussionmentioning
confidence: 99%